A review on making things see: Augmented reality for futuristic virtual educator - Iqbal J.; Sidhu M.S. (Taylor and Francis Ltd., 2023)
In the past few years many choreographers have focused upon implementation of computer technology to enhance their artistic skills. Computer vision technology presents new methods for learning, instructing, developing, and assessing physical movements as well as provides scope to expand dance resources and rediscover the learning process. This work reviews the study done over AR based learning technologies for the development of inter personal skills. This paper further elaborates the literature done till date within the scope of AR based training for educational aspects. The review focuses on the techniques categorized according to the type of dance learning method which can further be enhanced and addressed by means of novel AR based technology. The authors aim to provide an overview for learning standards based on AR Kinect sensors. In addition the future work is toward exploring the latest version of Kinect V2 for dance training that could become the next futuristic virtual educator. 2017 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.